Digital Political Participation, Social Networks and Big Data - Robles-Morales, José Manuel. author. aut Link
XI, 151 p. 10 illus., 1 illus. in color.
Keywords: This book explores the changes in political communication in light of the development of a public opinion mediated by web 2.0 technologies. One of the most important changes in political communication is related to the process of disintermediation, i.e. the process by which digital technologies allow citizens to compete in the public space with those agents who, traditionally, co-opted public opinion. However, while disintermediation has undeniably generated a number of advances, having linked citizens to the public debate, the authors highlight some aspects where disintermediation is moving away from a rational and inclusive public space. They argue that these aspects, related to the immediacy, polarization and incivility of the communication, obscure the possibilities for democratization of digital political communication. José Manuel Robles-Morales is a lecturer at the Sociology III Department at Complutense University, Spain. His research focuses on digital political participation, digital political theory, and technological differences (digital divide). His publications have appeared in journals such as Information Communication and Society, The European Journal of Communication Research, Revista Internacional de Sociología and Revista Española de Investigaciones Sociológicas. Ana María Córdoba-Hernández is Research and Faculty Head at the Faculty of Communication at the University of La Sabana, Colombia. Her research focuses on media, specifically in the context of international communication, digital political participation, the transformation of the network society and the analysis of socio-political phenomena across social networks.